فاعلية الذات العربية في تأصيل العلوم الغربية: قراءة في أعمال الرواد من جامعات بلاد يوربا- نيجيريا (Arabic as a viable tool for deepening western oriented knowledge: reading into the works of teachers of arabic in conventional universities, South-west, Nigeria) (2020)
This paper explores the viability of Arabic as an efficacious tool for the acquisition of western oriented knowledge. This is done by investigating into the learning backgrounds of selected University teachers of Arabic in Yorubaland. The study, using both analytical and descriptive methods samples works of seven personalities. It is discovered that majority of the scholars under the study had no opportunity to attend pre-university schools but had to sacrifice their little time unconventionally to measure up with their peers with basic western education whose medium of instruction is English. Following their academic attainment, they contributed not only to da’wah, for which they trained hitherto, but also propagation of Yoruba culture through translation and publications. The paper concludes that their seamless intellectual migration is levered by their previous knowledge of the language of Quran.